La desprotección del estado a las victimas de abuso sexual infantil - Cedeño Iturralde, Elsa Carolina (2013)
The present thesis before obtaining a law degree from the Courts of the Republic of Ecuador, was to structure a proposed amendment to Section 74 of the Code of Children and Adolescents, is performed following the procedure methodological and the provisions of Quevedo State Technical University, Faculty of Law. The culling of bibliographic material allowed me to make a historical analysis, and legal doctrine and comparative law and hypothesize theme to guide the field research. The theoretical framework of the thesis structured where detailed historical background, doctrine, jurisprudence and comparative law which determines the applicability of Article 74 of the Code of Children and Adolescents to punish child sexual abuse. In the field research based on surveys of citizens of Quevedo Canton, with the answers given by them, it was presented to demonstrate the need for reform of Article 74 of the Code of Children and Adolescents, contrary to that stated in the Constitution of the Republic of Ecuador articles 44 and 45. In legal analysis of child sexual abuse, coupled with the data provided in the field research through surveys of citizens and citizens of Quevedo Canton, comes to testing the hypothesis conclude that it is necessary to amend Article 74 of the Code of Children and Adolescents.